Áudio games no processo de aprendizagem de deficientes visuais: análise sob o aspecto da mediação da informação - Girão, Igor Peixoto Torres (2018)
Analyzes audio games in the teaching-learning process of visually impaired students. It problematizes the lack of accessibility in information mediation techniques, showing the DosVox audio games as a key in the information mediation process for these students. Informational practices derived from Information Science provide learning environments with new ways of working, interacting and giving meaning to information constructs. It reflects on the concepts of disability and visual impairment, without losing sight of the audio games, presented in parallel to games and video games. It reflects on the potential of sounds as an actor in the construction of senses and the mediation of information, as the sharing of sensations can be perceived through sonority and how DosVox audio games make use of this mechanics. Considering the reflections and problematizations made on audio games and how they can be used as mediation tools, it’s ask: how can audio games be a tool for mediation of information in the context of teaching and learning of students with visual impairment? To answer the question, we established the general objective: to evaluate the possibilities and use of DosVox audio games as a tool for mediation of information in the context of teaching and learning according to the teachers' view. The specific ones are: To evaluate and to discriminate the resources of the audio games of the DosVox, as far as the process of mediation of the information regarding the teaching and learning of visually impaired people; To analyze and characterize the perception of teachers and students of DosVox in the applicability of audio games as a tool for mediation of information in the context of teaching and learning of the visually impaired; To identify how the DosVox audio games constitute an accessible tool, Taking into account the way in which the audio of these games helps the teacher to establish a channel of information mediation with the students, using the concept of Dialogic Mediation (GOMES , 2014) highlighting the potential of the information professional as a mediator (ALMEIDA JÚNIOR, 2009; 2015) and with concepts about games by Huizinga (1999), Caillois (1990) and Cris Crawford (1982). This research is qualitative and is based on three methodological moments. The first one consists of a bibliographical and exploratory review, approaching and colliding arguments related to the themes addressed throughout the investigation. The second one is the compilation of 6 guidelines that show guidelines for the technical design of accessible games, always with reference what Nielsem (1993) lists as Usability attributes. The third is an in-depth interview with teachers specializing in the education of the visually impaired and an activity with their students using audio games in a mediative moment intending to understand every moment of information mediation. The concluding reflections point to the use of DosVox audio games as an additional possibility to mediate information for visually limited students, pointing to this tool as an alternative to mitigate informational exclusion.